(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the issue of Cossack leaders of the middle XVII – end of XVIII cent. and their relations with Ukrainian elite of XX century. The author claims that Cossack leaders were considered to be national elite taking responsibility for strategic and tactical drawbacks in state formation process of the middle XVII – end of XVIII cent. The result of the miscalculation became loosing Ukraine’s state system under the blows of powerful external factors.